First Aid in Fainting People - Masriana, Masriana; Juliani, Afrida; Adeana, Fadilla Putri; Usiono, Usiono (AMK : Abdi Masyarakat UIKA, 2023)
There are still many children and even teenagers who do not have any knowledge about First Aid for Fainted People, there are still many who have problems practicing what should be done first in helping someone who is Fainting, therefore the author conducted research on First Aid for Fainted People. The aim is to provide more knowledge about First Aid for Fainted People. The methods used in this research are interviews, observation and documentation. The results of this research are that the cause of fainting is a lack of blood supply, so that the intake of oxygen and blood sugar to the brain is reduced. So the first aid that must be done is to give the patient a chance to breathe, position one hand perpendicular to the chest and the other hand bent towards the face, lift one leg that is further away from your position until it forms a 90 degree angle, try to wake it up. By shaking his body, calling his name in a loud voice, slowly patting him or using ADTD (lift your chin and press your forehead.